Analisis Kinerja Keuangan Pengelolaan Alokasi Dana Desa Berdasarkan Rasio Efektivitas Dan Rasio Pertumbuhan Periode (2019-2020) Pada Kantor Desa Kagungan Rahayu Kecamatan Menggala Kabupaten Tulang Bawang - Anggela, Dhea Ayu; Japlani, Ardiansyah (Jurnal Manajemen DIVERSIFIKASI, 2022)
FINANCIAL PERFORMANCE ANALYSIS FUND ALLOCATION MANAGEMENT VILLAGE BASED ON EFFECTIVENESS AND RATIOGROWTH PERIOD (2019-2020) (At the Kagungan Rahayu Village Office, Menggala District, Tulang Bawang Regency) By: Dhea Ayu Anggela, Dr. Bambang Suhada2, S.E., M.Sc., (2) Ardiansyah Japlani2, S.E,. M.BA., AWM npm. 17610066 ABSTRACT Dhea Ayu Anggela Npm. 17610066 Financial Performance Analysis of Village Fund Allocation Management Based on Effectiveness Ratio and Growth Ratio Period (2019-2020) (At the Kagungan Rahayu Village Office, Menggala District, Tulang Bawang Regency). Supervisor (1) Dr. Bambang Suhada, S.E., M.Sc., (2) Ardiansyah Japlani, S.E,. M.BA., AWM Good village financial management will affect the progress of a village. Village financial management not only requires reliable human resources but also must be supported by adequate finance. This study aims to determine. This research was conducted with the aim of measuring the Village Fund management system in Kagungan Rahayu Village, Menggala District, Tulang Bawang Regency. The type of research used is quantitative research because the data collected is in the form of numbers from the Village Fund Allocation (ADD) financial report in the Village Revenue and Expenditure Budget (APBDesa). The results of this study show that 1) The results show that the effectiveness ratio can be categorized as effective, the efficiency ratio is less efficient, the regional financial management independence ratio is still low, the activity ratio is not good, and the growth ratio is good. This research is the same as research conducted that the Financial Performance of Village Fund Allocation (ADD) at the Kagungan Rahayu Village office, Menggala District, Tulang Bawang Regency is classified as Effective 2) the calculation of the Growth Ratio can be seen that the Village Fund Allocation Income Growth Ratio (ADD) for the Kagungan Rahayu Village office finances Menggala sub-district, Tulang Bawang Regency in 2019-2020 experienced a decline and growth. The Village Fund Allocation (ADD) expenditure for the Kagungan Rahayu Village office, Menggala sub-district, Tulang Bawang Regency showed positive and negative growth. Keywords: Effectiveness Ratio, Growth Ratio